Answer:
WWhat
Step-by-step explanation:
Answer:
y = (5/6)x - 7
is with
y = - (6/5)x + 1
y = - (5/6)x - 8
is with
y = (6/5)x - 5
y = - (7/4)x - 1
is with
y = (4/7)x + 9
y = (7/4)x - 2
is with
y = - (4/7)x + 2
Step-by-step explanation:
You can double check by dividing -1 by the number before x. The answer from that calculation will be the number before the x of the perpendicular line's equation
Answer:46
Step-by-step explanation:
The equation of a line is:
y = mx + c
The m is the gradient of the line, and the c is the y-intercept of the line
That means that the y-intercept of [y = -4x + 3] is 3
and the y-intercept of [y = -4x + 4] is 4
So the distance between the two y-intercepts is:
4 - 3 = <u>1</u>
Answer: 2
explanation: they’re both one place down